Straightforward Procedure for Laboratory Production of DNA Ladder - Vo Thi Thuong Lan; Pham Thi Thanh Loan; Pham Anh Thuy Duong; Le Thi Thanh; Ngo Thi Ha; Ta Bich Thuan (Journal of Nucleic Acids)
DNA ladder is commonly used to determine the size of DNA fragments by electrophoresis in routine molecular biology laboratories. In this study, we report a new procedure to prepare a DNA ladder that consists of 10 fragments from 100 to 1000 bp. This protocol is a combination of routinely employed methods: cloning, PCR, and partial digestion with restriction enzymes. DNA fragments of 100 bp with unique restriction site at both ends were self-ligated to create a tandem repeat. Once being cloned, the tandem repeat was rapidly amplified by PCR and partially digested by restriction enzymes to produce a ladder containing multimers of the repeated DNA fragments. Our procedure for production of DNA ladder could be simple, time saving, and inexpensive in comparison with current ones widely used in most laboratories.